Outcomes of Operative Treatment of Displaced Intra-articular Calcaneal Fracture in Adult - Mohammed Abdullah Abubaker; Sherwan Ahmed Ali Hamawandi; Abdulkadr Muhammed Sleman Alany (Advanced Medical Journal)
Background and objectives: Management of calcaneal fractures is controversy. Many options of treatment have been described, but there is no agreement about absolute indications. A study of the functional outcome is carried out in surgically treated intra articular calcaneal fracture in this prospective study. We studied the functional outcomes and postoperative complications including; infection, impingement, varus, Synovitis and flap necrosis in operative management of intra articular calcaneal fracture.